The Effect of Fly Swatter Game Toward Students’ Vocabulary Mastery - Suhendra, Kadek Krisna A. (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
Vocabulary mastery is a crucial foundation for elementary students studying any language, including English. The typical problems that cause students to lack vocabulary are that they easily become bored when the teacher explains things, that they believe acquiring language only entails understanding its meaning, and that they exclusively acquire vocabulary from their textbooks. On the other hand, many studies show that using games can improve vocabulary mastery, but most studies on this teaching method are not conducted with elementary students, especially considering that previously, English was not a compulsory subject in the elementary school curriculum as far as the Indonesian EFL context is concerned. To fill this gap, this study examines whether the use of this method has an impact on the vocabulary mastery of elementary students. The study was an-experiment study involving 26 students from a state elementary school in Tabanan Regency, Bali. Using descriptive and inferential (paired t-test) statistics, this study concluded that the use of the fly swatter game had a significant effect on the students' vocabulary mastery which was indicated by a significant increase in student scores after being given the teaching treatment using the fly swatter game. Regarding this result, it is suggested that elementary school teachers consider using the fly swatter game when teaching vocabulary to their students.